2010
DOI: 10.1016/j.ejvs.2010.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Skin Iron Deposition Characterises Lipodermatosclerosis and Leg Ulcer

Abstract: Iron overload is not present in the less severe stages of skin damage due to CVD but lipodermatosclerosis and leg ulcers are always accompanied by haemosiderin deposition. In fact, no severe skin changes occur in CVD legs until iron overload occurs. Our results are in agreement with previous reports suggesting that a genetic inability to counteract skin iron overload is present in these patients. A more detailed analysis of disordered iron metabolism should be undertaken in CVD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 27 publications
2
50
0
1
Order By: Relevance
“…Macrophage iron can be further increased during inflammation by virtue of increased systemic or local hepcidin expression, which leads to reduction in ferroportin, an iron efflux protein, resulting in intracellular iron accumulation. Individuals may also be predisposed to CVD disease through a genetic inability to counteract the skin iron overload (Caggiati et al, 2010). Studies have shown that common hemochromatosis gene mutations such as the C282Y mutation significantly increase the risk of ulcer in CVD by almost seven times (Zamboni et al, 2005).…”
Section: Deleterious Effects Of Local Cutaneous Iron Depositionmentioning
confidence: 99%
“…Macrophage iron can be further increased during inflammation by virtue of increased systemic or local hepcidin expression, which leads to reduction in ferroportin, an iron efflux protein, resulting in intracellular iron accumulation. Individuals may also be predisposed to CVD disease through a genetic inability to counteract the skin iron overload (Caggiati et al, 2010). Studies have shown that common hemochromatosis gene mutations such as the C282Y mutation significantly increase the risk of ulcer in CVD by almost seven times (Zamboni et al, 2005).…”
Section: Deleterious Effects Of Local Cutaneous Iron Depositionmentioning
confidence: 99%
“…4,5 Common clinical findings in chronic lipodermatosclerosis include hyperpigmentation, small white-scarred areas ("atrophie blanche"), localized skin induration, small ulcerations, and erythematous plaques in patients who have chronic venous insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, our present observation does not support an association of local leg skin damage with a systemic iron overload, as determined by serum ferritin levels. Probably in these latter cases vast amounts of metabolically active excess iron deposits in the organism are bound peripherally in the tissues in the form of hemosiderin [37], e.g. locally in the dermis of the legs.…”
Section: Discussionmentioning
confidence: 99%